Controllable crumpling of N-doped graphene induced by capillary force resistance. Issue 90 (14th September 2016) - Tang, Zhihong; Li, Xiaodong; Han, Zhuo; Yao, Long; Shen, Shuling; Yang, Junhe
Abstract : N doped crumpled graphene (NCG) with controllable morphology and opened structure is achieved by using urea as both soft template and nitrogen supplier. Abstract : Turning the 2D nanosheets into three-dimensional (3D) crumpled balls driven by the capillary force arising from water surface tension has proved to be an effective way to solve restacking. However, such a spherical form has a closed structure and the utilization of the inner surface is limited. Preparing crumpled graphene with an open structure, which can improve the utilization of the inner surface as well as maintain the excellent dispersion ability, is still a challenge. Herein, N-doped crumpled graphene (NCG) with controllable morphology and open structure is achieved by heating a microdroplet containing graphene oxide (GO) and urea; GO is the precursor of crumpled graphene and urea acts as both soft template to control the morphology of graphene and the nitrogen donor after template removal. ​N-doped crumpled graphene (NCG) with controllable morphology and open structure is achieved by heating a microdroplet containing graphene oxide (GO) and urea; GO is the precursor of crumpled graphene and urea acts as both soft template to control the morphology of graphene and the nitrogen donor after template removal. During the drying process, GO diffuses on the liquid–vapor interface and urea is adsorbed on the surface of GO driven by its different diffusion rate and free energy reduction. Results indicate that when the mass ratio of urea to GO is less than 10, a completely crumpled ball is formed; an open structure is obtained at the mass ratio of 100; a semi-open NCG ball is collected when the mass ratio is 50. NCG with different morphologies shows different dispersibility and electrochemical performance. The NCG ball can be dispersed in almost all the selected solvents, semi-open and open NCG can be dispersed in the majority of solvents, but the open one precipitates faster than the semi-open NCG. Semi-open NCG demonstrates better electrochemical performance than that of the crumpled NCG ball and open NCG because of its higher effective surface area and suitable morphology.